2012
DOI: 10.2214/ajr.11.7662
|View full text |Cite
|
Sign up to set email alerts
|

Second Opinion Interpretations by Specialty Radiologists at a Pediatric Hospital: Rate of Disagreement and Clinical Implications

Abstract: Our findings suggest that discrepancy rates for second interpretations in studies of pediatric patients transferred to tertiary care pediatric institutions are substantial. Although the original and second interpretations in the majority of cases were in agreement, major discrepancies were prevalent--12.6% and 32.6% of neuroimaging and body studies, respectively--and the second interpretations were significantly correlated with the final diagnosis. These results indicate that interpretations by subspecialty ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 8 publications
2
38
0
3
Order By: Relevance
“…Gollub et al reported on 143 body CT scans reinterpreted at a tertiary care cancer centre and found major disagreements between initial and second-opinion interpretations of 24/143 (17%) scans; the disagreements led to changes in management in 5/143 (3.5%) patients [10]. Eakins et al analyzed 733 paediatric cases for which diagnostic imaging examinations were re-reviewed at a paediatric hospital; they found major discrepancies between initial and second-opinion reports for 168 (21.7%) examinations [8]. The second-opinion interpretations were more accurate than the initial reports in 83 (90%) of 92 discrepant cases with proven diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Gollub et al reported on 143 body CT scans reinterpreted at a tertiary care cancer centre and found major disagreements between initial and second-opinion interpretations of 24/143 (17%) scans; the disagreements led to changes in management in 5/143 (3.5%) patients [10]. Eakins et al analyzed 733 paediatric cases for which diagnostic imaging examinations were re-reviewed at a paediatric hospital; they found major discrepancies between initial and second-opinion reports for 168 (21.7%) examinations [8]. The second-opinion interpretations were more accurate than the initial reports in 83 (90%) of 92 discrepant cases with proven diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Eakins et al [18] analyzed 733 pediatric cases that had been reinterpreted at a pediatric hospital. For 83 of 92 patients (90%) with major discrepancies for whom final diagnoses were independently proven, the second-opinion report was more accurate than the initial interpretation [18].…”
Section: Wibmer Et Almentioning
confidence: 99%
“…In this study the tumor staging was changed based on the expert opinion of the neuroradiologist in 56 % of cases and the recommended tumor management was changed in 38 % of cases. In a study by Eakens in 2012, a highly specialized subgroup of pediatric radiologists was examined regarding the effect of the their second opinion [4]. A lack of agreement between the initial report and the second opinion of the pediatric radiologists was detected here in 41.8 % of cases in 773 examined radiology reports.…”
Section: Discussionmentioning
confidence: 95%